The COWIN portal – current update, personal experience and future possibilities - Gupta, Mukund; Goel, Akhil Dhanesh; Pankaj Bhardwaj (Indian Journal of Community Health, 2021)
India began one of the biggest COVID-19 vaccination drives on 16 January 2021, marking the beginning of the mammoth effort to vaccinate more than 1.3 billion people. The vaccination programme to protect people has started globally to combat the pandemic, which has killed more than 3.1 million people globally and infected 149 million people as of 29 April (1). India started its vaccine drive with two vaccines- Covishield by the Serum Institute of India and Covaxin by Bharat Biotech. Around 12,000 private hospitals, empanelled under PM-JAY (National Health Insurance), and hospitals under the CGHS (Central Government Health Scheme) are the vaccination sites. The monitoring of inoculation drive and to track the listed beneficiaries on a real-time basis, Co-WIN application has been developed for planning, implementation, monitoring, and evaluation of the whole drive in India. This software was developed by Union Health Ministry, and their experience with electronic Vaccine Intelligence Network (eVIN) software has ensured the versatility and utility of this dedicated Co-WIN software(2)